Peripheral Neuropathy Associated With Ipilimumab: A Report of 2 Cases. Issue 2 (February 2015) - Thaipisuttikul, Iyavut; Chapman, Paul; Avila, Edward K.
Abstract : Ipilimumab, a monoclonal antibody targeting human cytotoxic T-lymphocyte–associated antigen 4, was approved by the FDA and European Medicines Agency for the treatment of metastatic melanoma. Immune-related adverse effects can occur with the use of this agent, but peripheral nervous system problems are rare. We report 2 cases of ipilimumab-induced polyneuropathy.